Media-Independent Multicast Signalling for Enhanced Video Performance in the MEDIEVAL Project - Corujo, Daniel (2011)
With the foreseen major increase in video traffic over the coming years, the current Internet’s design is being perceived as inefficient for handling the demanding flow of video over wireless access networks, populated by an ever increasing number of mobile terminals. The MEDIEVAL project aims to evolve the current Internet architecture to provide an optimized video support in all layers of the protocol stack. With its cross-layer approach, abstraction mechanisms such as IEEE802.21 will work as enablers between the different architecture modules. With the widespread diffusion of video being realized over multicast and broadcast channels for resource optimization, using 802.21 signalling to optimize handovers affecting groups of users will generate multiple messages to each individual terminal. In this article, we extend 802.21 to support multicast transport of its signalling, enabling more efficient group handover scenarios.